Occurrence of Strongylid Nematode Parasites on Horse Farms in Berlin and Brandenburg, Germany, With High Seroprevalence of Strongylus vulgaris Infection - Jürgenschellert, Laura; Krücken, Jürgen; Bousquet, Eric; Bartz, Jürgen; Heyer, Nina; Nielsen, Martin K.; von Samson-Himmelstjerna, Georg (Frontiers in Veterinary Science, 2022)
Infection of horses with strongylid nematodes are highly prevalent with multi-species infections being the rule. Strongylus spp. and in particular Strongylus vulgaris are amongst the most pathogenic strongyle equine parasites. Presumably due to regular strategic anthelmintic treatments in combination with long prepatencies, prevalence of these worms was severely reduced in past decades. In this study, 484 horses from 48 farms in Berlin/Brandenburg, Germany were sampled between May 2017 and January 2018. Mini-FLOTAC and combined sedimentation/flotation were used to analyse faecal samples and larval cultures were carried out from individual, strongyle infected horses for molecular testing for Strongylus spp. infection. Additionally, for S. vulgaris, antibodies against a recombinant larval antigen were quantified in an ELISA. Strongyle type eggs were detected in 66.7% of individual faecal samples. Nematode DNA was amplifiable from 311 samples and S. vulgaris and Strongylus edentatus were detected in four (1.3%) and 10 (6.3%) of these, respectively, the latter using a novel high-resolution-melt PCR targeting S. edentatus, Strongylus equinus and Strongylus asini. On the farm level, prevalence for Strongylus spp. by PCR was 12.5%. Applying a conservative cut-off (sensitivity 0.43, specificity 0.96), 21.2% of all serum samples were positive for antibodies against S. vulgaris larvae (83.3% prevalence on farm level). Newly developed pyrosequencing assays to analyse putatively benzimidazole resistance associated polymorphisms in codons 167, 198 and 200 of the isotype 1 β-tubulin gene of S. vulgaris did not detect such polymorphisms in the four positive samples. Low age and increasing access to pasture were risk factors for egg shedding and seropositivity for S. vulgaris. Time since last treatment increased whereas use of moxidectin and ivermectin for the last treatment decreased the risk for strongyle egg shedding. Noteworthy, horses under selective treatment had significantly higher odds to be seropositive for anti-S. vulgaris antibodies than horses treated four times per year (odds ratio 4.4). The serological findings suggest that exposure to S. vulgaris is considerably higher than expected from direct diagnostic approaches. One explanation is contamination of the environment by few infected horses leading to infection of many horses with larvae that never reach maturity due to regular anthelmintic treatments.